2011
DOI: 10.1007/s13225-011-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of drug discovery from fungi

Abstract: For the past 50 years, fungal secondary metabolites have revolutionized medicine yielding blockbuster drugs and drug leads of enormous therapeutic and agricultural potential. Since the discovery of penicillin, the first β-lactam antibiotic, fungi provided modern medicine with important antibiotics for curing life threatening infectious diseases. A new era in immunopharmacology and organ transplantation began with the discovery of cyclosporine. Other important drugs or products for agriculture derived from or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
112
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 173 publications
(117 citation statements)
references
References 189 publications
0
112
0
1
Order By: Relevance
“…Multidrug resistant strains of M. tuberculosis demands new drugs to restrain the spreading control of tuberculosis. The natural system always serve as a repository and generally mankind always looks into actinomycetes (Mahajan et al, 2011;Adegboye and Babalola, 2013;Patel et al, 2014), fungi (Smith and Ryan 2009;Aly et al, 2011), cyanobactria (Singh et al, 2011) and plants (Abdallah, 2011;Katiyar et al, 2012) for the new drug candidates. Numerous drugs and chemical agents have already been identified and the identification process is still on ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Multidrug resistant strains of M. tuberculosis demands new drugs to restrain the spreading control of tuberculosis. The natural system always serve as a repository and generally mankind always looks into actinomycetes (Mahajan et al, 2011;Adegboye and Babalola, 2013;Patel et al, 2014), fungi (Smith and Ryan 2009;Aly et al, 2011), cyanobactria (Singh et al, 2011) and plants (Abdallah, 2011;Katiyar et al, 2012) for the new drug candidates. Numerous drugs and chemical agents have already been identified and the identification process is still on ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytes provide an abundant reservoir of bioactive metabolites for medicinal exploitation, and an increasing number of novel compounds are being isolated from endophytic fungi. The endophytic fungi natural products present a broad spectrum of activities such as antimicrobial (Aly et al, 2011), antioxidant (Jalgaonwala et al, 2017), immunosuppressive properties, antivirals (Strobel, et al, 2003), anticholinesterase (Aly et al, 2011), antineoplasic (Zhang et al, 2006;Shweta et al, 2010) and cytotoxic activities (Aly et al, 2011). Some studies have shown that endophytic fungi can produce many important bioactive secondary metabolites, such as Taxol (R) from the endophytic fungus Taxomyces andreanae and vincristine isolated from the endophytic fungus Fusarium oxysporum, which are important anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Various fungi are also used for biotransformation of steroids that have been extensively used in medicine. [3][4][5] Currently, microorganisms are used for synthesis of nanoparticles within green nanotechnology; biosynthesis of gold, silver, gold-silver alloy, selenium, tellurium, platinum, palladium, silica, titania, zirconia, quantum dots, magnetite and uraninite nanoparticles by Aspergillus sp., Colletotrichum sp., Fusarium sp., Neurospora sp., Penicillium sp., Phoma sp., Trichoderma sp., Verticillium sp., yeasts and other fungal species has been reported. [6,7] Fungi are ubiquitous in nature and vital for recycling of nutrients contained in organic matter.…”
Section: Introductionmentioning
confidence: 99%